Recent progress in atmospheric sciences : applications to the Asia-Pacific region - Liou, Kuo-Nan; Chou, M. D. (Ming-Dah) (World Scientific Pub., 2008)
This book contains 22 peer-reviewed articles that cover a spectrum of contemporary subjects relevant to atmospheric sciences, with specific applications to the Asia-Pacific region. The majority of these papers consist of a review of a scientific sub-field in atmospheric sciences, while some contain original contributions. All of the accepted papers were subject to scientific reviews and revisions.